História da Arte Técnica: um olhar contemporâneo sobre a práxis das Ciências Humanas e Naturais no estudo de pinturas sobre tela e madeira - Alessandra Rosado (2011)
This study aims to epistemologically characterize the emergent field of study in Brazil named Technical Art History that gathers research methods of History, Art History, physical-chemical analysis and Conservation Science applied to cultural goods. The classical theories of Humanities (especially Art History) and Natural Sciences (Physics, Chemistry and Biology) are analyzed in order to investigate through thecontributions of these areas in the process of restoration, authentication and the study of painting techniques and materials on canvas and wood the points of contact in the conformation of interdisciplinary practice proposed by the Technical Art History. The presented case studies regarding the oil painting on canvas by Poussins authorship, the anonymous work O Lenhador (The Woodman) and the preliminary study of materials and techniques of the Candido Portinari works allowedto assess the general constitution lines of this new practice (where different history stages of production of a work of art can often be revealed, providing important information about the creative process of an artist and his/her intentions) and proceed with the proposition of establishing a dialogue, ideally without any barriers, between the Human and Natural Sciences.